Verbal Abuse by Parents: Its Relationship with Children's Self-esteem, Anxiety, Depression, and Behavior - Jamari, Nor Laili-Azua (Universiti Sains Malaysia, 2009)
In order to enhance our understanding of verbal abuse, the current study provides an overview of the impact of parental verbal abuse on children. This study examines the relationship between parental verbal abuse with children's self-esteem, anxiety, depression and behavior. A sample of 302 Malay children is selected from an apartment complex in a residential area of Petaling Jaya. A questionnaire was used to measure the frequency of verbal abuse received by the children from their parent, and measure the symptoms of self esteem, anxiety, depression, and behavioral problem occur in children. The data were coded and analyzed by using SPSS Version 12 involving the usage of three statistical analyses, which are Spearman's rho Correlation analysis, Mann-Whitney U Test, and Wilcoxon Signed Rank Test. The result of the analysis shows that verbal abuse by parents were associated with children's self-esteem, anxiety, depression, and behavior. Findings from the present study indicated that the mother is more significantly verbalized the children compared to the father. The result also a showed significant difference between genders in children's anxiety, depression, and behavior. On the other hand, the finding showed a significant difference between age group in children's anxiety and depression score. For gender and age differences, the result showed no significant difference in parental verbal abuse.